Developing a Conversational Virtual Standardized Patient to Enable Students to Practice History-Taking Skills. Issue 2 (April 2017) - Maicher, Kellen; Danforth, Douglas; Price, Alan; Zimmerman, Laura; Wilcox, Bruce; Liston, Beth; Cronau, Holly; Belknap, Laurie; Ledford, Cynthia; Way, David; Post, Doug; Macerollo, Allison; et al.
Abstract : Introduction: Although traditional virtual patient simulations are designed to teach and assess clinical reasoning skills, few employ conversational dialogue with the patients. The virtual standardized patients (VSPs) described herein represent standardized patients that students interview using natural language. Students take histories and develop differential diagnoses of the VSPs as much as they would with standardized or actual patients. The student-VSP interactions are recorded, creating a comprehensive record of questions and the order in which they were asked, which can be analyzed to assess information-gathering skills. Students document the encounter in an electronic medical record created for the VSPs. Methods: The VSP was developed by integrating a dialogue management system (ChatScript) with emotionally responsive 3D characters created in a high-fidelity game engine (Unity). The system was tested with medical students at the Ohio State University College of Medicine. Students are able to take a history of a VSP, develop a differential diagnosis, and document the encounter in the electronic medical record. Results: Accuracy of the VSP responses ranged from 79% to 86%, depending on the complexity of the case, type of history obtained, and skill of the student. Students were able to accurately develop an appropriate differential diagnosis on the basis of the information provided by the patient during the encounter. Conclusions: The VSP enables students to practice their history-taking skills before encounters with standardized or actual patients. Future developments will focus on creating an assessment module that will automatically analyze VSP sessions and provide immediate student feedback.